1980
DOI: 10.1111/j.1365-2125.1980.tb04842.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐ethnic and inter‐phenotype differences among Ghanaians and Caucasians in the metabolic hydroxylation of phenytoin [proceedings]

Abstract: on a t.l.c. plate with methanol as solvent, and this produced a peak which corresponded to an EE sulphate marker. The second aliquot (100,l) was incubated with sulphatase (5 u) and saccharo-lactone (2 mg) in acetate-buffer (450 el; pH 5.0) and the third aliquot (100 isl) was incubated with ,B-glucuronidase (3500 u The rate of excretion of PHP in the EM subjects was faster than that in the PM individuals (Figure 1) and the difference was significant. Each Ghanaian subject displayed approximately constant rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Of special interest is a study of phenytoin oxidation in Ghanaians and Caucasians in relation to the status of debrisoquine hydroxylation capacity (Andoh et al, 1980). In each population, poor metabolisers of debrisoquine excreted somewhat less p-hydroxyphenytoin in their urine than did the extensive metabolisers.…”
Section: Debrisoquinementioning
confidence: 99%
“…Of special interest is a study of phenytoin oxidation in Ghanaians and Caucasians in relation to the status of debrisoquine hydroxylation capacity (Andoh et al, 1980). In each population, poor metabolisers of debrisoquine excreted somewhat less p-hydroxyphenytoin in their urine than did the extensive metabolisers.…”
Section: Debrisoquinementioning
confidence: 99%
“…A. J. H. Critchley et al been reported in Caucasians. Ghanaians have a reduced capacity for the hydroxylation of debrisoquine (Woolhouse et al, 1979) and possibly phenytoin (Andoh et al, 1980) but not nortriptyline (Woolhouse et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The metabolism of a number of drugs has been shown not to co-segregate with that of SP/DB (Brssen & Gram 1989). Initial reports of a significant relationship between debrisoquine 4-hydroxylation and phenytoin p-hydroxylation seen in both Caucasians and Ghanaians (Andoh et al 1980) have not been confirmed (Roots et al 1985;Steiner et al 1987). In a second example, a ten fold higher excretion of the sulphoxide metabolites of carbocysteine in EMS compared to PMs (Waring et al 1981) was subsequently shown to be a chance observation but with a probability of P < 0.001 (Haley et al 1985).…”
Section: Population Panel and Family Studies Of Sparteine And Debrismentioning
confidence: 98%